A4.19 The quantification of digital activity fluorescence optical imaging of hand and wrist inflammation in rheumatic diseases. (13th February 2015) - Kisten, Y; Györi, N; af Klint, E; Rezaei, H; Levitsky, A; Karlsson, A; van Vollenhoven, R
Abstract : Background and objectives: The objective detection and quantification of disease activity in its earliest pathophysiological stage is critical for achieving optimal therapy results. Fluorescence optical imaging (FOI) is a novel imaging modality for the hands and wrists, and automated quantification of the ensuing images using DACT (Disease ACTivity)-FOI as a novel algorithm representing activity. This study was designed to determine the utility of FOI as a diagnostic tool, and whether it could be used in lieu of colour/power Doppler ultrasound (US) to quantify and ascertain apparent and non-apparent active synovitis Materials and methods: A total of 872 hand/wrist joints in 26 patients (18 female, 8 male, average age 51.5 years) with various rheumatic diseases (RA: 12, JIA, SLE, DM, FM, PsA and polyarthritis 1–2 each) were examined by standard clinical assessment, US and DACT-FOI. Joints swollen and tender or swollen only were considered clinically inflamed. Active synovitis was defined as having synovial thickening and Doppler activity on US. Joints positive by FOI displayed abnormal focal optical intensities by visual inspection. Silent synovitis was defined as showing synovitis by US but not clinically. The DACT value was digitally quantified per patient by an automated computer-based algorithm of the composite image (240 frames). After clinical, US and FOI positive joints for each hand were calculated, the sensitivity, specificity and kappa statistics computed and compared with the mean DACT values for all patients Results: Out of 872 joints, 142 (16%) were inflamed clinically, 241 (28%) by US, and 229 (26%) by FOI. There was moderate agreement for synovitis detection between clinical examination and US (kappa 0.524 ± 0.033; 95% CI: 0.459–0.589) and between clinical examination and FOI (kappa 0.450 ± 0.035; 95% CI: 0.381–0.519). Of the 241 inflamed joints by US, 196 (81%) were also inflamed by FOI, while only 119 (49%) were inflamed clinically. Agreement between US and FOI in synovitis detection was good (kappa 0.773 ± 0.024; 95% CI: 0.725–0.821). Depending on the gold standard used to define inflammation, FOI was 73%–83% sensitive and 86%–95% specific for detecting synovitis. Out of 730 non-inflamed joints by clinical examination, 608 (83%) were non-inflamed by US and 605 (83%) were non-inflamed by FOI. Of these clinically non-inflamed joints, 122 (17%) were inflamed by US. For detecting silent synovitis, FOI was 80% (98/122) sensitive and 96% (581/608) specific. The number (mean ± SD) of active joints detected by clinical, US and FOI was 5.4 ± 7.6; 9.4 ± 9.8; and 9.3 ± 9.7 respectively, and the overall automated disease activity DACT-FOI was 4.3 ± 2.1. There was a strong positive correlation (r = 0.556; p = 0.003) between the clinical detection of synovitis and DACT-FOI. The mean DACT values also correlated significantly with US (r = 0.479; p = 0.013) and semi-quantitative FOI (r = 0.515; p = 0.007) Conclusion: FOI and the automated analysis DACT-FOI were technically feasible with high reproducibility and agreement with clinical scoring and US. For detecting synovitis semi-quantitatively, FOI had a lower sensitivity but similar specificity compared to US. FOI may be particularly useful in identifying patients with clinically non-apparent hand/wrist inflammation (silent synovitis).